2006
DOI: 10.1158/0008-5472.can-05-4065
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the RNA Splicing Machinery as a Novel Treatment Strategy for Pancreatic Carcinoma

Abstract: Aberrant patterns of pre-mRNA splicing have been established for many human malignancies, yet the mechanisms responsible for these tumor-specific changes remain undefined and represent a promising area for therapeutic intervention. Using immunohistochemistry, we have localized the expression of a central splicing regulator, serine-arginine protein kinase 1 (SRPK1), to the ductular epithelial cells within human pancreas and have further shown its increased expression in tumors of the pancreas, breast, and colon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
102
1
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 32 publications
(40 reference statements)
9
102
1
6
Order By: Relevance
“…6F). These observations corroborate the genetic evidence that SRPKs are major kinases for SR proteins in mammalian cells as their siRNA-mediated down-regulation (Hayes et al 2006) or inactivation by homologous recombination (P.-P. Wang and X.-D. Fu, unpubl.) both attenuated SR protein phosphorylation.…”
Section: Splice Site Selection In Response To Altered Cellular Distrisupporting
confidence: 85%
See 1 more Smart Citation
“…6F). These observations corroborate the genetic evidence that SRPKs are major kinases for SR proteins in mammalian cells as their siRNA-mediated down-regulation (Hayes et al 2006) or inactivation by homologous recombination (P.-P. Wang and X.-D. Fu, unpubl.) both attenuated SR protein phosphorylation.…”
Section: Splice Site Selection In Response To Altered Cellular Distrisupporting
confidence: 85%
“…It is thus not surprising that experimental induction of both hypo-and hyperphosphorylation of SR proteins frustrates this cycle and inhibits splicing, an outcome that underscores the requirement for precise regulation of SR protein phosphorylation in the cell (Prasad et al 1999). Despite that multiple protein kinases and phosphatases have been implicated in SR protein phosphorylation and dephosphorylation, only SRPK1 and PP1 have been characterized by RNAi-mediated knockdown (Hayes et al 2006;Shi and Manley 2007). While a recent study demonstrated the activation of PP1 by stripping off a heatshock-sensitive PP1 inhibitor and showed that the phosphorylation state of different SR proteins is controlled by both activated PP1 and differential accessibility of SR protein kinases (Shi and Manley 2007), little is known about how specific SR kinases might be regulated under physiological conditions.…”
Section: Physiological Importance To Regulate Sr Protein Phosphorylatmentioning
confidence: 99%
“…34,35 However, the molecular mechanisms involved in such processes remain largely unknown. Importantly, and consistent with a function of SR proteins during the response to DNA damage, it has been previously shown that SC35 accumulates following g-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is noteworthy that the SR protein kinase 1, a key regulator of SRSF1 activity, is also upregulated in PDAC 28 and was proposed as a suitable target for novel therapies. 29 In conclusion, our study identifies a novel pro-survival pathway triggered by gemcitabine in PDAC cells, which relies on MNK2-dependent phosphorylation of eIF4E, and suggests that targeting this pathway might represent a promising approach to enhance the response of PDAC cells to therapeutic agents.…”
Section: Inhibition Of Mnk Activity Enhances Gemcitabine-induced Apopmentioning
confidence: 68%